PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL PEMERINTAH DAERAH KABUPATEN MALUKU BARAT DAYA - Leunupun, Engrith Grafelia; Heumesse, Piter (Jurnal Akuntansi Kompetif, 2024)
This research aims to analyze the influence of Regional Original Income and Special Allocation Funds on Capital Expenditures. This research is a type of quantitative research with the data used is secondary data in the form of reports on the realization of the regional government budget of Southwest Maluku Regency from 2016-2022. Data testing was carried out using SPSS to test the hypothesis. The results obtained from this test are that local original income does not have a significant and partial effect on capital expenditure and special allocation funds partially and significantly have an effect on capital expenditure, and simultaneously there is an influence between local original income and special allocation funds on capital expenditure.